2014
DOI: 10.1002/etc.2647
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of bisphenol A and cadmium on growth and nitrate assimilation of soybean seedling roots

Abstract: Bisphenol A (BPA) and cadmium (Cd) pollution exist simultaneously in many regions. However, little information is available regarding the combined effects of BPA and Cd pollution on plants. Plant roots are in direct contact with the soil, which is an important compartment of BPA and Cd. In the present study, the effects of combined BPA and Cd pollution on soybean seedling roots were evaluated in pot experiments. Combined treatment with BPA and Cd at low concentrations (1.5 mg/kg BPA and 0.2 mg/kg Cd) improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although BPA is expected to be degraded quickly, it is ubiquitous in some natural environments owing to its continuous input. Recent studies have shown that BPA has inevitably influenced the balance of the ecosystem, having seriously threatened environmental safety . Among the soil ecosystems, nematodes are the most abundant metazoan in soil with high environmental relevance, playing a key role in decomposition, nutrient cycling, and maintenance of environmental quality.…”
Section: Introductionmentioning
confidence: 99%
“…Although BPA is expected to be degraded quickly, it is ubiquitous in some natural environments owing to its continuous input. Recent studies have shown that BPA has inevitably influenced the balance of the ecosystem, having seriously threatened environmental safety . Among the soil ecosystems, nematodes are the most abundant metazoan in soil with high environmental relevance, playing a key role in decomposition, nutrient cycling, and maintenance of environmental quality.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have indicated that bisphenols affect ecosystem balance and threaten environmental safety (Ike et al ; Ji et al ; René and Watson ; Hu et al ; Sun et al ), but studies on the comparative toxicity of bisphenol analogs are limited. In the soil ecosystem, nematodes are the most abundant metazoan, with a high response to perturbations; they play a key role in nutrient cycling, decomposition, and environmental quality maintenance.…”
Section: Introductionmentioning
confidence: 99%